Biomasa y calidad nutritiva de leptochloa crinita en la región semiárida pampeana (Argentina) - Ruiz, Maria De Los Angeles; Gonzalez, Martín; Ernst, Ricardo; Ortiz, Daniela Alejandra (COPROCNA, 2022)
Poster